2018
DOI: 10.1126/scitranslmed.aam7710
|View full text |Cite
|
Sign up to set email alerts
|

Antibody blockade of IL-15 signaling has the potential to durably reverse vitiligo

Abstract: Vitiligo is an autoimmune disease of the skin mediated by CD8 T cells that kill melanocytes and create white spots. Skin lesions in vitiligo frequently return after discontinuing conventional treatments, supporting the hypothesis that autoimmune memory is formed at these locations. We found that lesional T cells in mice and humans with vitiligo display a resident memory (T) phenotype, similar to those that provide rapid, localized protection against reinfection from skin and mucosal-tropic viruses. Interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(239 citation statements)
references
References 47 publications
9
230
0
Order By: Relevance
“…Moreover, in human melanoma, local IL‐15 levels strongly correlated with tumor‐resident CD8 + T‐cell numbers, and high IL‐15 levels were associated with a more favorable prognosis (Edwards et al, ). IL‐15 seems to be essential in retaining T cells within the tumor microenvironment, indicating that IL‐15 is worthy of further investigation, as supported by the murine vitiligo data discussed previously (Richmond, Strassner, Zapata, et al, ).…”
Section: Skin‐resident T‐cell Responses In Melanomasupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, in human melanoma, local IL‐15 levels strongly correlated with tumor‐resident CD8 + T‐cell numbers, and high IL‐15 levels were associated with a more favorable prognosis (Edwards et al, ). IL‐15 seems to be essential in retaining T cells within the tumor microenvironment, indicating that IL‐15 is worthy of further investigation, as supported by the murine vitiligo data discussed previously (Richmond, Strassner, Zapata, et al, ).…”
Section: Skin‐resident T‐cell Responses In Melanomasupporting
confidence: 55%
“…T RM cell formation has been shown to be highly dependent on IL‐15, and IL‐15 promoted T RM cell function ex vivo (Adachi et al, ; Mackay et al, ). A subsequent study therefore looked at IL‐15 signaling as a therapeutic target for vitiligo (Richmond, Strassner, Zapata, et al, ). Treatment with anti‐CD122 antibody, a subunit of the IL‐15 receptor on human and mouse T RM cells, was shown to reverse disease in mice with established vitiligo (Figure ).…”
Section: The Role Of Trm Cells In Autoimmune Vitiligomentioning
confidence: 99%
“…Pmel‐1 CD8 + T cells are recruited into the skin as early as 1 week after vitiligo induction (unpublished observation), but infiltration peaks at 5 to 7 weeks after induction. We have found that Pmel‐1 CD8 + T cells remain in the skin until the end of natural life as resident memory CD8 + T cells (Richmond et al., ). Between 10 and 12 weeks after vitiligo induction some wild‐type SCF mice spontaneously repigment, and the reasons behind this are unknown.…”
Section: Commentarymentioning
confidence: 99%
“…Spots of depigmentation appear as early as 3 to 4 weeks and continue to develop in severity over time. SCF mice reach a plateau of vitiligo around 7 to 8 weeks, after which the disease stabilizes, and the majority of Pmel‐1 adopt a resident memory phenotype defined as CD103 + CD69 + CD44 + CD62L – (Richmond et al., ).…”
Section: Commentarymentioning
confidence: 99%
“…Factors that induce upregulation of CD69 expression include TNF‐α and type I interferons . As an example, strategies targeting IL‐15 could be promising to inhibit the generation of T RM ; however, it is still unknown whether a targeted antibody can efficiently deplete T RM cells located into the skin, as recently shown with the use of an antibody directed against CD122, the β subunit of the IL‐15 receptor expressed on T RM cells . However, human data are still lacking to confirm these results obtained in a mouse model of depigmentation.…”
Section: Looking For Early Intervention In Vitiligomentioning
confidence: 99%